Estudio de la comunicación intercultural en la divulgacion de las costumbres y tradiciones autóctonas de la Comunidad Montuvia del Recinto Lechugal del cantón Ventanas, año 2021 - Velasquez Leones, Leidy Lisbeth (2021)
Investigate the Study of Intercultural Communication and its impact on the dissemination of indigenous customs and traditions of the Montuvian community of the “Lechugal” area of the Ventanas canton. The methodology used in the research work was two important qualitative and quantitative approaches in order to detail in a more strict and convenient way the problem that exists, and to be able to propose feasible solutions. Participatory and field research was applied to obtain pertinent and timely information from the citizens of the Lechugal Enclosure. The inductive and deductive method was used to establish the influence of intercultural communication on the quality of life of the citizens of the enclosure. The types of techniques such as survey and observation, adding the questionnaire as an instrument, were applied in order to familiarize with the citizens of the Lechugal area, and thus collect information with greater precision, showing how intercultural communication benefits or harms community development. Within the research work, 120 citizens were determined as a population and 92 citizens of the Lechugal area were determined by calculating the sample. In which the acceptance of the proposals and recommendations was favorably concluded, it was also determined that with the application of intercultural communication the customs and traditions of the Montuvian community of the Lechugal area of the Ventanas canton can be rescued.